Paradoxical effects of optogenetic stimulation in mesial temporal lobe epilepsy. Issue 5 (27th August 2019) - Lévesque, Maxime; Chen, Li‐Yuan; Etter, Guillaume; Shiri, Zahra; Wang, Siyan; Williams, Sylvain; Avoli, Massimo
Abstract : Objective: To establish the effects induced by long‐term, unilateral stimulation of parvalbumin (PV)‐positive interneurons on seizures, interictal spikes, and high‐frequency oscillations (80–500Hz) occurring after pilocarpine‐induced status epilepticus (SE)—a proven model of mesial temporal lobe epilepsy (MTLE)—in transgenic mice expressing or not expressing ChR2. Methods: PV‐ChR2 (n = 6) and PV‐Cre (n = 6) mice were treated with pilocarpine to induce SE. Three hours after SE onset, unilateral optogenetic stimulation (450nm, 25mW, 20‐millisecond pulses delivered at 8Hz for 30 seconds every 2 minutes) of CA3 PV‐positive interneurons was implemented for 14 continuous days in both groups. Results: Rates of seizures ( p < 0.01), interictal spikes ( p < 0.001), and interictal spikes with fast ripples (250–500Hz) ( p < 0.001) were lower in PV‐ChR2 than in PV‐Cre mice. Ripples (80–200Hz) occurring outside of interictal spikes had higher rates in the PV‐ChR2 group ( p < 0.01), whereas isolated fast ripples had lower rates ( p < 0.01). However, seizure probability was higher during optogenetic stimulation in PV‐ChR2 compared to PV‐Cre animals ( p < 0.05). Interpretation: Our findings show that the unilateral activation of CA3 PV‐positive interneurons exerts anti‐ictogenic effects associated with decreased rates of interictal spikes and fast ripples in this MTLE model. However, PV‐positive interneuron stimulation can paradoxically trigger seizures in epileptic animals, supporting the notion that γ‐aminobutyric acid type A signaling can also initiate ictogenesis. ANN NEUROL 2019;86:714–728